Enhanced view of the" tropical atlantic ozone paradox" and "zonal wave-one" from the in-situ MOZAIC and SHADOZ data. - (:unkn) unknown (My University, 2006)
Ozone vertical profiles from the Measurements of Ozone from Airbus In-service Aircraft (MOZAIC) program over Africa are used to complement pictures of the wave-one pattern and the “tropical Atlantic paradox” identified through soundings in the Southern Hemisphere Additional Ozonesondes (SHADOZ) network. The Atlantic paradox refers to a greater tropospheric ozone column amount over the South Atlantic than the North Atlantic during the West African biomass burning season. SHADOZ and MOZAIC data from 1998–2002 and 1997–2004, respectively, are used to show that these two phenomena are linked. The combined data are used to address the following: Does the (continental) MOZAIC data modify the appearance of the paradox? Do lower tropospheric MOZAIC data lead to new conclusions about ozone in the wave-one maximum region? During December, January, and February (DJF), the lower troposphere over Africa exhibits a higher ozone signal in the burning hemisphere, that is, north of the equator, so the “paradox” does not appear over the African continent. The MOZAIC data set over Africa highlights another component of the wave-one feature when the tropospheric ozone mixing ratio is viewed in zonal cross section. The lower troposphere makes a nonnegligible contribution to the regionally higher ozone column during the biomass burning periods of each hemisphere (DJF) for West Africa and June, July, and August (JJA) for the central Africa region. A southern preference for the wave-one character, previously deduced from satellite data, is confirmed with a stronger maximum in September, October, and November (SON). Both the paradox and wave-one phenomena are consistent with a view that the African continent is a major source of biomass burning and lightning emissions.
Keywords: African Research